Characterization of Vibrio cholerae’s Extracellular Nuclease Xds - Pressler, Katharina; Mitterer, Fabian; Vorkapic, Dina; Reidl, Joachim; Oberer, Monika; Schild, Stefan (Frontiers in Microbiology, 2019)
The Gram-negative bacterium Vibrio cholerae encodes two nucleases, Dns and Xds, which play a major role during the human pathogen’s lifecycle. Dns and Xds control three-dimensional biofilm formation and bacterial detachment from biofilms via degradation of extracellular DNA and thus contribute to the environmental, inter-epidemic persistence of the pathogen. During intestinal colonization the enzymes help evade the innate immune response, and therefore promote survival by mediating escape from neutrophil extracellular traps. Xds has the additional function of degrading extracellular DNA down to nucleotides, which are an important nutrient source for V. cholerae. Thus, Xds is a key enzyme for survival fitness during distinct stages of the V. cholerae lifecycle and could be a potential therapeutic target. This study provides detailed information about the enzymatic properties of Xds using purified protein in combination with a real time nuclease activity assay. The data define an optimal buffer composition for Xds activity as 50 mM Tris/HCl pH 7, 100 mM NaCl, 10 mM MgCl2, and 20 mM CaCl2. Moreover, maximal activity was observed using substrate DNA with low GC content and ambient temperatures of 20–25°C. In silico analysis and homology modeling predicted an exonuclease domain in the C-terminal part of the protein. Biochemical analyses with truncated variants and point mutants of Xds confirm that the C-terminal region is sufficient for nuclease activity. We also find that residues D787 and H837 within the predicted exonuclease domain are key to formation of the catalytic center.